2017
DOI: 10.1089/bfm.2016.0150
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Breastfeeding Training Techniques for Primiparous Mothers Before Discharge on the Incidence of Cracked Nipples

Abstract: The results documented that breastfeeding training based on one-to-one demonstration utilizing specially designed audiovisual tools was more effective than the other two methods in the prevention of nipple cracks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
7
0
8
Order By: Relevance
“…The opportunity to experience, as close to reality as possible, helps puerperal women understand and adequately replicate breastfeeding technique. 15 Low-cost training with minimal technology was offered to 603 pregnant women in the third trimester, increased confidence regarding breastfeeding (p=0.05) and provided sufficient knowledge in the postpartum period (p=0.02) However, training was insufficient to increase the duration of breastfeeding or reduce breast problems. 31 Conversely, two studies, one with moderate (S2) and the other with high (S3) recommendation, showed that health education on breastfeeding in the postpartum period, with emphasis on the correct breastfeeding technique is not more effective in preventing nipple trauma than the regular guidance provided at the maternities.…”
Section: Health Education On Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…The opportunity to experience, as close to reality as possible, helps puerperal women understand and adequately replicate breastfeeding technique. 15 Low-cost training with minimal technology was offered to 603 pregnant women in the third trimester, increased confidence regarding breastfeeding (p=0.05) and provided sufficient knowledge in the postpartum period (p=0.02) However, training was insufficient to increase the duration of breastfeeding or reduce breast problems. 31 Conversely, two studies, one with moderate (S2) and the other with high (S3) recommendation, showed that health education on breastfeeding in the postpartum period, with emphasis on the correct breastfeeding technique is not more effective in preventing nipple trauma than the regular guidance provided at the maternities.…”
Section: Health Education On Breastfeedingmentioning
confidence: 99%
“…13 Thus, health education on breastfeeding plays an important role in minimizing problems related to breastfeeding. 9,14,15 The performance of health workers in the prevention of nipple trauma is still a challenge 16 and a scientific basis from the best evidence is needed to support decision-making in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…По некоторым данным, наличие трещин на соске в послеродовом периоде в 95% слу-чаев приводит к отказу от грудного вскармливания [11,12]. По данным A. Eksioglu и соавт., трещины сосков наблюдались у 20% женщин с индивидуальным кон-сультированием по грудному вскармливанию, у 57% женщин, получивших информацию из обучающей лите-ратуры, и у 63% женщин, ознакомленных с вопросами грудного вскармливания в дородовом периоде на тео-ретических групповых занятиях [13]. В исследовании Y. Prasad и соавт.…”
Section: Introductionunclassified
“…При наличии травматизации соска инфициро-вание в первый месяц лактации отмечалось в 37% слу-чаях (на момент обращения и перед обращением к врачу по клинической картине, описываемой пациенткой), что является угрозой возникновения маститов в каждом третьем случае [13].…”
Section: Introductionunclassified
“…Na Turquia, estudo de intervenção realizado na cidade de Izmir, que investigou os efeitos de diferentes técnicas de treinamento de amamentação na incidência de mamilos rachados para mães primíparas antes da alta hospitalar, encontrou que a taxa de mamilos rachados foi inferior nas mães que receberam treinamento baseado na demonstração (p <0,05), quando comparada às mães que receberam apenas atendimento de rotina ou folhetos informativos. Apesar disso, não houve diferença significante na prevalência de AME às 2 e 4 semanas após o parto entre os grupos (Eksioglu et al, 2017). De acordo com Santos et al (2016), técnicas precárias de amamentação e nascimento em hospital não credenciado como HAC, entre outras características, associam-se à maior prevalência de mamilos rachados.…”
Section: Esta é a Primeira Coorte De Nascimentos De Base Populacionalunclassified